A case report of neonatal orbital peripheral primitive neuroectodermal tumor and literature review. Issue 5 (September 2021) - Li, Yian; Chen, Lian; Zhou, Xiaohong; Gao, Lu; Cai, Xiaojing; Yang, Chenhao; Hu, Lan
Primitive neuroectodermal tumors are rare malignant neoplasms from primitive neural crest cells. Most primitive neuroectodermal tumors occur in the central and sympathetic nervous systems. We report a Chinese newborn patient presenting a huge unilateral proptosis after birth, diagnosed as orbital peripheral primitive neuroectodermal tumor by histopathology and immunohistochemistry. Our case is the first reported case of orbital peripheral primitive neuroectodermal tumor diagnosed in the newborn period. The clinical manifestations, radiological findings, histopathologic, and immunohistochemistry results are described in detail. We also conducted a literature search focusing on primitive neuroectodermal tumor of the orbit. To the best of our knowledge, all articles with English abstracts were reviewed here.